2013
DOI: 10.2131/jts.38.823
|View full text |Cite
|
Sign up to set email alerts
|

Methylmercury induces caspase-dependent apoptosis and autophagy in human neural stem cells

Abstract: Methylmercury (MeHg) is a well-known human neurotoxic agent whose exposure sources are mainly environmental and aquatic-derived food. MeHg is reported to induce central nervous system disability. However, the exact mechanism of MeHg-induced neurotoxicity is still unknown. In this study, to investigate which cell death signaling pathway is related with MeHg-induced cytotoxicity, the effects of MeHg on apoptosis and autophagy were evaluated in HB1.F3 human neural stem cells (NSCs). Human NSCs were treated with 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 44 publications
2
32
0
Order By: Relevance
“…In our study, only MeHg showed cytotoxic and growth‐inhibitory effects on IMR‐32 cells in a time‐ and concentration‐dependent manner, which has also been demonstrated in previous studies using various in vitro models (Chang et al, ; Petroni et al, ). The cells exposed to HT did not show any alteration in cell viability, which is supported by a previous report (Zhu et al, ) wherein human retinal pigment epithelial cells were used as an in vitro model to study the protective efficacy of HT against oxidative stress.…”
Section: Discussionsupporting
confidence: 89%
“…In our study, only MeHg showed cytotoxic and growth‐inhibitory effects on IMR‐32 cells in a time‐ and concentration‐dependent manner, which has also been demonstrated in previous studies using various in vitro models (Chang et al, ; Petroni et al, ). The cells exposed to HT did not show any alteration in cell viability, which is supported by a previous report (Zhu et al, ) wherein human retinal pigment epithelial cells were used as an in vitro model to study the protective efficacy of HT against oxidative stress.…”
Section: Discussionsupporting
confidence: 89%
“…The fact that autophagy in neonatal rat primary astrocytes is activated by MeHg is thus not surprising. Induction of both autophagy and apoptosis by MeHg has been described in human neural stem cells via the AKT-mTOR pathway and caspase-dependent apoptosis (Chang et al 2013). In addition, inorganic mercury has been shown to induce autophagy in rat hepatocytes treated in vitro (Chatterjee et al 2012, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, 1 μM CH 3 Hg was shown to inhibit retinoic acid induced neural differentiation within human NSCs over a 48 h culture period, via induction of caspase-dependent apoptosis (Chang et al, 2013). Single doses of CH 3 Hg (2.5 or 5 nM) drastically inhibited neuronal differentiation of primary embryonic rat cortical NSCs (bFGF omission, 120 h culture) (Tamm et al, 2006), compared to controls under similar conditions.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, methylmercury induced caspase-dependent apoptosis and autophagy in human NSCs within 48 h exposure at 1 μM dosage, via inhibition of Akt1/mTOR signaling (Chang et al, 2013). Although cadmium, methylmercury or lead did not activate caspase 3 or p53 (indicators of apoptosis) in human fetal cortex neuroprogenitor cells, exposure to cadmium or methylmercury doubled apoptotic cells within embryonic mouse cortical NSCs (Culbreth et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation